Implementation of Antam Gold Buying and Selling at ABC Gold Shop Pekanbaru From the Perspective of Maqashid Syariah, Especially in Protecting Property (Hifz Al-Mal) - Febrian Permana; Muhammad Albahi; Rustam (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the implementation of Antam gold buying and selling transactions at the ABC Pekanbaru gold shop from the perspective of Maqasid Sharia. Gold as a ribawi commodity has special provisions in its buying and selling practices, so a transaction mechanism is needed that is not only valid according to Islamic jurisprudence, but also able to realize benefits and avoid harm. The Maqasid Sharia approach, especially in safeguarding assets (hifz al-mal), is used to assess the suitability of gold transaction practices with the main objectives of Sharia. This study uses a qualitative method with a descriptive approach. Data were obtained through interviews with employees and customers of the ABC Pekanbaru gold shop, and supported by documentation. The analysis was carried out by linking field findings with the five objectives of Maqasid Sharia, namely protection of religion, life, mind, descendants, and property. The results show that protection of assets is a very prominent objective of Maqasid Sharia in gold buying and selling practices at the ABC Pekanbaru gold shop, this protection is realized through clear contracts, price transparency that follows market mechanisms, and the availability of buyback facilities that provide certainty of value and liquidity for customers. This mechanism protects customers from the risk of fraud and unreasonable losses, but based on the different views of Islamic scholars who require gold transactions to be carried out in cash and direct handover, the provision of cash transaction services is an important step to ensure that the assets owned by customers are truly protected from elements of usury and are valid according to Sharia.